2020
DOI: 10.1111/jan.14471
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a couple‐based psychosocial intervention on patients with prostate cancer and their partners: A quasi‐experimental study

Abstract: Aims: To understand the effectiveness of a couple-based psychosocial information package (PIP) and multimedia psychosocial intervention (MPI) on patients with prostate cancer and their partners. Design: A random assignment and quasi-experimental design were used. Methods: From August 2015-March 2018, 103 newly diagnosed patients with prostate cancer and their partners were divided into a control group (CG) (N = 50), PIP group (N = 25) and MPI group (N = 28). The CG received usual care, the PIP group received i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Twenty‐four of the included articles reported RCTs while four studies used a quasi‐experimental design to assess the effect of PEIs on caregiver outcomes 15,34–36 . The majority of the trials were conducted in the United States of America 37–46 with just one trial from France, 47 Nigeria, 36 and Taiwan 35 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐four of the included articles reported RCTs while four studies used a quasi‐experimental design to assess the effect of PEIs on caregiver outcomes 15,34–36 . The majority of the trials were conducted in the United States of America 37–46 with just one trial from France, 47 Nigeria, 36 and Taiwan 35 …”
Section: Resultsmentioning
confidence: 99%
“…The majority of interventions were delivered to caregivers in a group setting, 15,36,50,51,55,60 others were delivered individually 34,37–39,42,43,45–49,52,54,56–59,61 and one study administered intervention to the patient‐caregiver dyad 35,40,44 . Interventions varied in duration, ranging from 1 contact session 47 to 10 contact sessions, 43,60 over 2 weeks 40 to 1 year 37 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Web‐based PCa education has also been helpful in improving QoL and reducing treatment side effect symptoms (Song et al, 2015). Researchers have also shown that use of media can be helpful in an intervention (e.g., Chien et al, 2020). Web‐based PCa education would be especially beneficial for those African American PCa couples who find the idea of engaging in traditional counseling intimidating or who may be hesitant to discuss issues related to PCa (Rivers et al, 2012).…”
Section: Recommendations For Interventionsmentioning
confidence: 99%